calculus5

(y^2+2)^3=x^4y+e^2 find dy/dx using differentiating implicity

  1. 👍 0
  2. 👎 0
  3. 👁 104
asked by Ivan
  1. Damon and I have done some of them for you.
    Now you try some of the others.
    Post your solution so we can see where your difficulty is.
    These are rather straightforward questions, and you should not expect us just to do the work for you.

    1. 👍 0
    2. 👎 0
    posted by Reiny
  2. I understand what you guys think I am a soldier on duty and I have to turn these in I am runnning out of time and I need help
    thanks

    1. 👍 0
    2. 👎 0
    posted by Ivan

Respond to this Question

First Name

Your Response

Similar Questions

  1. calculus3

    x^2/3+y^2/3=5 find dy/dx using differentiating implicity

    asked by Ivan on November 28, 2010
  2. calculus2

    x^2+2y^2-11=0 find dy/dx using differentiating implicity

    asked by Ivan on November 28, 2010
  3. calculus1

    x^5-5y=6-x find dy/dx using differentiating implicity

    asked by Ivan on November 28, 2010
  4. calculus4

    2y^3-y=7-x^4 find dy/dx using differentiating implicity

    asked by Ivan on November 28, 2010
  5. Calculus

    6x-3y=4 find dy/dx using differentiating implicity

    asked by Ivan on November 28, 2010
  6. Calculus

    Find the derivative of the function y, below. It may be to your advantage to simplify before differentiating. y = 8x(ln(x)+ln(2))-4x+pi

    asked by Nate on October 14, 2013
  7. Math

    Find the general antiderivative of f (x) and check your answer by differentiating. f(x) = x^5 + 9 Need Help.

    asked by Jason on July 1, 2010
  8. Calculus

    Find the derivative of f. you may simplify before differentiating f(x)= x2-7x+12/x4-8x3+13x2+30x-72

    asked by HELP!! on March 9, 2011
  9. Maths

    How would you solve this in order to find t? 0.2t(t-5.1)(t-9.1)=2.4+0.75t I tried differentiating it, but I wasn't getting the answer I was supposed to

    asked by alicia on October 9, 2015
  10. Calculus

    Integrate x dx/(1-x). I have proceeded thus- Int xdx/(1-x)=int -(x-1+1)/(x-1) =-Int[1+ 1/(x-1)]dx =-Int dx-Int dx/(x-1) =-x-log(x-1). On differentiating, we get original expression- d/dx[-x-log(x-1)]=-1-1/(x-1)=-x/(x-1)=x/(1-x).

    asked by MS on January 8, 2014

More Similar Questions